The characteristics of antireflux surgery compared to proton pump inhibitor treatment in Korea: a nationwide study using claim data from 2007 to 2016 - Park, Susan (Ann Surg Treat Res, 2020)
PURPOSE: Laparoscopic antireflux surgery is not widely used in Korea, but published data suggest that its results are comparable to those of Western countries. The purpose of this study was to compare the clinical characteristics, medical utilization, and medical costs of antireflux surgery and proton pump inhibitor (PPI) treatments. METHODS: We used Korean patients who underwent fundoplication (n = 342, surgery group) and a 25% random sample of all patients diagnosed with gastroesophageal reflux disease (GERD) who were prescribed PPIs for more than 12 weeks (n = 130,987, medication group) between 2007 to 2016. We compared medical costs and utilization between the 2 groups. RESULTS: The average cost of fundoplication was $4,631. The costs of GERD treatment in the first year after surgery and during the follow-up period were $78.1 and $50.1 per month, respectively. In the surgery group, the average monthly medical expenses decreased as the year progressed, but the average monthly medical expenses ($137.5 per month) did not decrease in the medication group. After stratifying by age group, the medical costs of the surgery group were lower than those of the medication group for all ages except for patients between the ages of 70 and 79. The cost difference between the 2 groups was prominent between the ages of 20 and 49. CONCLUSION: This study showed that a significant decrease in cost was observed 1 year after surgery, and it was more apparent in younger patients. Further research is needed to determine the appropriateness of antireflux surgery for each group of patients.